Language practices in multilingual writing processes – Supporting reflection in a complex modern world - Dengscherz, Sabine (Jurnal Ilmu Pendidikan, 2023)
This article presents and discusses a model for the reflection of language practices in (academic) writing processes: The Resources Interrelations Model (RIM) aims at a deeper understanding of the functional application of language resources in (demanding) text production. It addresses influence factors that interfere with individual language practices and locates them on four layers: First, the writing process and its situational demands, second, individual attitudes, goals, and motivation, third, individual language and writing biographies and fourth, societal background (including the ongoing technology development and AI tools). The RIM is a theoretical model; however, it is inspired by empirical research in the PROSIMS project. In my article, I present and describe the RIM and its four layers, sketch its points of departure, and locate the model in its interdisciplinary discursive context, in particular referring to process-oriented writing research and research on multilingualism (including poststructuralist criticism of language categories). Additionally, I outline the relevance of such a model as a starting point for further research and a base for the (self-) reflection of writing processes. As the model focuses on the interrelation of influence factors (instead of specific writing strategies), it is open for individual and situational variation and for the dynamic changes in a complex modern world, while at the same time providing a framework for systematic analysis.